Compatibility assessment of a temperature-controlled radiofrequency catheter with a novel electroanatomical mapping system - Pannone, Luigi; Eltsov, Ivan; Ramak, Robbert; Cabrita, David; De Letter, Paul; Chierchia, Gian-Battista; de Asmundis, Carlo (Frontiers in Cardiovascular Medicine, 2023)
Background The novel DiamondTemp ablation system (DTA) and EnSiteX mapping System (EAM) are both CE-Marked and FDA approved medical devices. The DTA has been validated by its manufacturer only in combination with previous version of EnSite System—EnSite Precision. The aim of this study was to evaluate compatibility of DTA with EnSite X with a previously developed protocol. Methods Three configurations were tested: 3.1. Medtronic Generator connection Box (GCB) and AmpereConnect cable; 3.2. the Medtronic GCB-E and electrogram out cable from GCB to EAM; 3.3. Direct connection of DTA to EAM using intracardiac out cable with no GCB. Results The previously developed universal method for compatibility assessment of ablation catheters and navigation systems was used with success for assessing DTA and EnSite X EAM compatibility, with reproducible results. Accuracy of DTA visualization with different setups was evaluated with a phantom model measuring distances between DTA and reference points. DTA is compatible with EnSiteX EAM with a safety and reliability profile guaranteed, if within the described specifications. In particular, careful setup is mandatory to achieve good clinical outcomes as only setup 3.2 is viable for both NavX and Voxel Mode and demonstrated satisfactory results and accuracy. Setup 3.3 showed a significant shift immediately after catheter insertion. Catheter position was away from baseline points and the dislocation increased during the radiofrequency delivery. Conclusions Previously developed method for compatibility assessment of ablation catheters and navigation systems has been used for a new EAM. DTA is compatible with EnSiteX EAM with proper configuration.